Identifying Current and Missing Knowledge in the Control of Pyrethroid-Resistant Triatoma Infestans, Vector of Chagas Disease - Roca Acevedo, Gonzalo (2017)
Triatomines are blood-sucking bugs that occur mainly in Latin America. They are vectors of Trypanosoma cruzi, the parasite that causes Chagas disease. Chemical control of Chagas disease´s vectors by using pyrethroid insecticides has been highly successful for the elimination of domestic infestation and consequently the reduction of the vector transmission. However, at the beginning of the 2000s a decrease in the effectiveness of the chemical control of triatomines was detected in several areas from Argentina and Bolivia, particularly in the Gran Chaco eco-region. During the last 15 years, several studies demonstrated the evolution of insecticide resistance in Triatoma infestans and established the presence of different toxicological profiles, the autosomal inherence of resistance, the biological costs of deltamethrin resistance, the expression of deltamethrin resistance thorough the embryonic development, and the main mechanisms of resistance (target-site insensitivity and metabolic detoxification of insecticides). The emergence of pyrethroid resistance coupled with the usual difficulties in sustaining adequate rates of insecticide applications emphasize the need of incorporating other tools for integrated vector and disease control, such as the proposal of the organo-phosphorus insecticide fenitrothion as an alternative chemical strategy for the management of the resistance because it was effective against pyrethroid-resistant populations in laboratory and semi-field trials. New studies on the current situation of presence and spread of resistant populations of triatomines and the acceptance of the use of alternative insecticides are critical requirements in the implementation of strategies for the management of resistance and for the rational design of campaigns oriented to reducing the vector transmission of Chagas’ disease.